Evaluation of Probiotics for Warfighter Health and Performance - Agans, Richard T.; Giles, Grace E.; Goodson, Michael S.; Karl, J. Philip; Leyh, Samantha; Mumy, Karen L.; Racicot, Kenneth; Soares, Jason W. (Frontiers in Nutrition, 2020)
The probiotic industry continues to grow in both usage and the diversity of products available. Scientific evidence supports clinical use of some probiotic strains for certain gastrointestinal indications. Although much less is known about the impact of probiotics in healthy populations, there is increasing consumer and scientific interest in using probiotics to promote physical and psychological health and performance. Military men and women are a unique healthy population that must maintain physical and psychological health in order to ensure mission success. In this narrative review, we examine the evidence regarding probiotics and candidate probiotics for physical and/or cognitive benefits in healthy adults within the context of potential applications for military personnel. The reviewed evidence suggests potential for certain strains to induce biophysiological changes that may offer physical and/or cognitive health and performance benefits in military populations. However, many knowledge gaps exist, effects on health and performance are generally not widespread among the strains examined, and beneficial findings are generally limited to single studies with small sample sizes. Multiple studies with the same strains and using similar endpoints are needed before definitive recommendations for use can be made. We conclude that, at present, there is not compelling scientific evidence to support the use of any particular probiotic(s) to promote physical or psychological performance in healthy military personnel. However, plausibility for physical and psychological health and performance benefits remains, and additional research is warranted. In particular, research in military cohorts would aid in assessing the value of probiotics for supporting physical and psychological health and performance under the unique demands required of these populations.